Climate change and banking sector (in)stability in Kenya: A vulnerability assessment - Gillian Kimundi; Reuben Wambui (Kenya Bankers Association (KBA), 2023)
This paper offers a climate change vulnerability assessment of the Kenyan banking sector by examining the time-varying linkages of climate risk drivers, economic sectors that get impacted by a disorderly low-carbon transition (climate policy relevant sectors (CPRSs)), and banking sector stability. We use temperature and precipitation climate data, identify 5 CPRSs and their quarterly outputs, construct a banking sector stability index, and examine the time-varying linkages of these variables. Effectively, we assess the response of banking sector stability to sectoral output shocks arising from physical and transition risks. Three important findings emerge: First, the agriculture sector is the sole channel of physical climate risk transmission. Second, manufacturing and utilities sectors are becoming increasingly critical/significant channels for transmitting transition risks. Third, during the COVID-19 era, all CPRSs have become increasingly linked to banking sector stability, effectively exacerbating the transmission of climate risks to the banking sector.
Keywords: 330; climate change; climate risk drivers; climate policy relevant sectors (CPRS); banking sector; stability